Temperature control in sepsis - Doman, Marc; Thy, Michael; Dessajan, Julien; Dlela, Mariem; Do Rego, Hermann; Cariou, Erwann; Ejzenberg, Michael; Bouadma, Lila; de Montmollin, Etienne; Timsit, Jean-François (Frontiers in Medicine, 2023)
Fever can be viewed as an adaptive response to infection. Temperature control in sepsis is aimed at preventing potential harms associated with high temperature (tachycardia, vasodilation, electrolyte and water loss) and therapeutic hypothermia may be aimed at slowing metabolic activities and protecting organs from inflammation. Although high fever (>39.5°C) control is usually performed in critically ill patients, available cohorts and randomized controlled trials do not support its use to improve sepsis prognosis. Finally, both spontaneous and therapeutic hypothermia are associated with poor outcomes in sepsis.